21 Identifying Patients Pre-Tavi for Standard Indication for PPM Implantation May Reduce Post-Tavi Urgent Implantations Rates. (31st May 2014) - Phan, Thanh; Awan, Mohammad; Shome, Joy; James, Simon; Thornley, Andrew; de Belder, Mark; Linker, Nicholas; Muir, Dougie; Turley, Andrew
Abstract : Introduction: In high-risk patients with severe symptomatic aortic stenosis (AS) surgical AVR (sAVR) or Transcatheter Aortic Valve Implanation (TAVI) are established treatment options. Rates of permanent pacemaker (PPM) insertion post TAVI are dependent on valve type and vary from22.5% for Medtronic CoreValve to 5.9% for the Edwards heart valve system. We examined PPM rates in a real world registry of 136 consecutive TAVI patients to explore pre-TAVI and post-TAVI PPM implantation rates. We also used a comparator group of patients who underwent sAVR following heart team evaluation. Method: Our unit is a regional referral centre with a catchment population of 1.5 million. Data was collected prospectively on all patients with severe symptomatic AS assessed in our TAVI heart team MDT (between 2009–2012). TAVI indications were either logistic Euroscore >20% or inoperable status as judged by direct surgical review and heart team discussion. PPMs were implanted prior to TAVI if patients had class I or II indications for pacing. The Edwards Sapien or Sapien XT heart-valve system was used in all TAVI procedures. Prospectively collected data included: co-morbidities, logistic Euroscore, and incidence of urgent/emergency PPM implantation post procedure. Results: 136 patients underwent TAVI and 59 underwent sAVR following heart team review. TAVI patients were older and higher risk than sAVR patients (mean age 82 ± 7 vs 80yrs; mean log Euroscore 25 ± 13% vs 15 ± 9.7 %). Patients with existing PPM at baseline in the TAVI and sAVR cohort were 6.6% (n = 9) and 3.4% (n = 2), respectively. Six (4.4%) patients had a PPM electively implanted pre TAVI after heart team review. The incidence of PPM insertion following TAVI and sAVR was 3.7% (n = 5) and 5.1% (n = 3), respectively. In the TAVI cohort, three patients had PPM implanted peri-procedure and two were implanted within five days. sAVR patients had their PPM implanted electively at a mean 118 days post procedure. Conclusion/Implications: Standard indications for PPM insertion in elderly patients pre-TAVI are common. Our post TAVI pacing rates are low and compare favourably to those seen in tightly controlled clinical trials. Requirement for PPM insertion post TAVI is also similar to sAVR.